(untitled) (Tạp chí Y học Cộng đồng, 2025)
Objective: Describe clinical and paraclinical characteristics and treatment results of respiratory failure in newborns at the neonatal department of Xanh Pon General Hospital in 2023 - 2024. Subject and method: Study subjects: 258 medical records of neonates with respiratory distress treated at Xanh Pon General Hospital. Study design: Descriptive, retrospective data analysis. Results: In our study, the proportion of male neonates (67.4%) was higher than that of female neonates (32.6%) and was predominant in both age groups. Neonates ≤1 day old accounted for the majority (67.4%), while those >1 day old comprised 32.6%. The most common clinical sign of respiratory distress was tachypnea >60 breaths/min (79.5%), cyanosis (79.1%). Laboratory findings included leukopenia in 15.5%, anemia in 17.8%, and thrombocytopenia in 5.8% of neonates. Hypoalbuminemia was observed in 72.9%, hypoglycemia in 19.8%, and elevated CRP levels in 36%. The referral rate to higher-level hospitals was 1.9%. A high proportion of neonates with respiratory distress required respiratory support, with oxygen therapy being the most common (33.7%), followed by CPAP (22.5%) and mechanical ventilation (17.4%). All cases (100%) required antibiotic treatment. Conclusion: Respiratory distress in neonates presents with diverse clinical and paraclinical features, varying according to gestational age. The majority of affected neonates required respiratory support, yet most responded well to treatment.